2022
DOI: 10.3390/agronomy12030551
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Novel Endophytic and Rhizobacterial Strains Upregulates Antioxidant Enzyme Systems and Mineral Accumulation in Wheat

Abstract: Wheat is the third largest grown crop after maize and rice worldwide. Integrated use of chemical and biofertilizers have the potential to improve crop yield and quality due to their growth-promoting attributes. Therefore, the present study planned to evaluate the effectiveness of endophytic (Paenibacillus sp. strain (ZE11), Bacillus subtilis (ZE15) and Bacillus megaterium (ZE32)) and rhizobacterial strains (Bacillus subtilis (ZR2) Bacillus subtilis (ZR3) and Bacillus megaterium strain (ZR19)), solely and in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The bacterial population improved the amounts of nitrate-nitrogen, ammonium-nitrogen, and microbial biomass carbon [39]. This was also reported by Iqbal et al [40]. The treatments applied in our study showed a remarkable improvement in microbial carbon biomass and act as substrate for nutrient availability in soils, hence improving their biochemical properties and organic matter.…”
Section: Discussionsupporting
confidence: 88%
“…The bacterial population improved the amounts of nitrate-nitrogen, ammonium-nitrogen, and microbial biomass carbon [39]. This was also reported by Iqbal et al [40]. The treatments applied in our study showed a remarkable improvement in microbial carbon biomass and act as substrate for nutrient availability in soils, hence improving their biochemical properties and organic matter.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings were observed by Hammad et al [61], who used organic waste for the application of the PGPR consortium and found that the growth-promoting traits of the PGPR, such as miners solubilization, indole acetic acid (IAA) production, and siderophore production, not only enhanced the chlorophyll, MSI, RWC, and mineral nutrients, but also biofortify okra with Zn and Fe. The reason for this might be that the use of organic carriers with entrapped nutrients and microorganisms solubilizes mineral nutrients by secreting organic acids in the rhizosphere of spinach [62].…”
Section: Discussionmentioning
confidence: 99%
“…All of the carrier materials significantly enhanced the microbial population, but the treatment with peat had the maximum microbial count as compared to the other organic carriers. The reason for this might be the provision of a large surface area for microbial attachment to peat, their compatibility, and the ease of degrading the peat to attain energy and nutrients for their population growth, even under harsh climatic conditions [62]. The improved bacterial population is responsible for the enhanced-growth promoting activities, i.e., mineral solubilization, nutrient uptake, root proliferation, and water for better crop growth, as well as physiological trait improvements and, ultimately, yield improvement [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…To increase the natural fertility of the soil, it is necessary to introduce new technologies using biofertilizers of microbial origin to ensure the stability of crops. Currently, researchers around the world are paying attention to this issue [14][15][16].…”
Section: Mod Concep Dev Agronomentioning
confidence: 99%